FISCAL DECENTRALIZATION, GROWTH AND DISPARITY AMONG REGION IN INDONESIA - Rifa Surya (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2012)
One of the main reasons for decentralization in Indonesia was to provide every regions the same opportunity to develop themselves based on their needs. Ever since fiscal decentralization was implemented, the central government had conducted an intergovernmental transfer scheme to local governments, thereby transferring almost 30% of central government revenue to local governments. The purpose of this paper was to find evidence about the impact of fiscal decentralization in Indonesia and economic development indicators, namely growth and regional income disparity, during the period of observation, (1995–2008). The analysis was carried out using autonomy indicators, production indicators and expenditure per capita as fiscal decentralization measurement tools. A data panel approach was then implemented to find consistency in the effect of these indicators. The results showed that higher autonomy indicators which represent local government own source revenue were related to lower GDP per capita growth and higher regional income disparity after fiscal decentralization. Upgrading capacity and capability among bureaucrats at the local and central levels was recommended in order to achieve positive effects of decentralization. However, further research with comprehensive methods and fiscal decentralization measurement might still be needed to prove the precise effects of fiscal decentralization on economic development indicators in Indonesia.